2020
DOI: 10.3390/molecules25245849
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Oligosaccharide Degree of Polymerization on the Induction of Xylan-Degrading Enzymes by Fusarium oxysporum f. sp. Lycopersici

Abstract: Xylan is one of the most abundant carbohydrates on Earth. Complete degradation of xylan is achieved by the collaborative action of endo-β-1,4-xylanases and β-d-xylosidases and a number of accessories enzymes. In filamentous fungi, the xylanolytic system is controlled through induction and repression. However, the exact mechanism remains unclear. Substrates containing xylan promote the induction of xylanases, which release xylooligosaccharides. These, in turn, induce expression of xylanase-encoding genes. Here,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 94 publications
0
6
0
Order By: Relevance
“…It was found that xylooligo-saccharides were more effective than other substrates at the induction of β-xylosidases and endoxylanases. Moreover, xylotetraose, xylohexaose, and xylobiose were the best inducers of endoxylanase, extracellular β-xylosidase, and cell-bound β-xylosidase, respectively [147].…”
Section: Glycoside Hydrolasesmentioning
confidence: 96%
“…It was found that xylooligo-saccharides were more effective than other substrates at the induction of β-xylosidases and endoxylanases. Moreover, xylotetraose, xylohexaose, and xylobiose were the best inducers of endoxylanase, extracellular β-xylosidase, and cell-bound β-xylosidase, respectively [147].…”
Section: Glycoside Hydrolasesmentioning
confidence: 96%
“…Xylan is the most known polymer belonging to the hemicellulose polysaccharide family. Xylan molecule has 1–4 xylopyranosyl linked to α-4-O-methyl-D-glucuronopyranosyl units and is a branched-chain polymer having a 5-carbon sugar monomer [ 53 ]. Most of the hemicellulose is soluble in alkaline solvents.…”
Section: Value-added Products From Lcb Componentsmentioning
confidence: 99%
“…As mentioned before, complete degradation of xylan is achieved by a variety of modular enzymes. Although many hemicellulolytic enzymes have been studied extensively, little is known about how microorganism cells sense the presence of xylan and uptake hemicellulose-derived products ( Polizeli et al, 2005 ; Delmas et al, 2012 ; Najjarzadeh et al, 2020 ). The induction signal for the synthesis of xylanolytic enzymes is supposed to involve transporters of xylose and short XOS released by the action of little amounts of the enzymes produced constitutively, along with lactose, glucose, and even cellulose, that are able to cross the membrane and induce the regulatory machinery ( Biely and Petráková, 1984 ; Royer and Nakas, 1989 ; Chandra Raj and Chandra, 1995 ; Christakopoulos et al, 1996a , 1996b ; Kulkarni et al, 1999 ), which suggests a complex induction mechanism of xylanases.…”
Section: Xylanolytic Enzyme Systemsmentioning
confidence: 99%
“…According to their findings, the overall strategy appears to be an induction of a specific, small scale, sensory response by the onset of carbon starvation, mediated at least partially by alleviation of CreA-dependent catabolite repression, that triggers the release of a small subset of degradative enzymes which initiate degradation on a small scale, in turn releasing sugars that cause the fungus to express its full degradative arsenal ( Delmas et al, 2012 ). More recently, Najjarzadeh and collaborators reported that xylotetraose is more effective than other substrates inducing endoxylanase, while xylohexaose and xylobiose are the best inducers of extracellular β-xylosidase, and cell-bound β-xylosidase, respectively ( Najjarzadeh et al, 2020 ).…”
Section: Xylanolytic Enzyme Systemsmentioning
confidence: 99%